FAAH and CNR1 Polymorphisms in the Endocannabinoid System and Alcohol-Related Sleep Quality - Soundararajan, Soundarya; Kazmi, Narjis; Brooks, Alyssa T.; Krumlauf, Michael; Schwandt, Melanie L.; George, David T.; Hodgkinson, Colin A.; Wallen, Gwenyth R.; Ramchandani, Vijay A. (Frontiers in Psychiatry, 2021)
Sleep disturbances are common among individuals with alcohol use disorder (AUD) and may not resolve completely with short-term abstinence from alcohol, potentially contributing to relapse to drinking. The endocannabinoid system (ECS) is associated with both sleep and alcohol consumption, and genetic variation in the ECS may underlie sleep-related phenotypes among individuals with AUD. In this study, we explored the influence of genetic variants in the ECS (Cannabinoid receptor 1/CNR1: rs806368, rs1049353, rs6454674, rs2180619 and Fatty Acid Amide Hydrolase/FAAH rs324420) on sleep quality in individuals with AUD (N = 497) and controls without AUD (N = 389). We assessed subjective sleep quality (from the Pittsburgh Sleep Quality Index/PSQI) for both groups at baseline and objective sleep efficiency and duration (using actigraphy) in a subset of individuals with AUD at baseline and after four weeks of inpatient treatment. We observed a dose-dependent relationship between alcohol consumption and sleep quality in both AUD and control groups. Sleep disturbance, a subscale measure in PSQI, differed significantly among CNR1 rs6454674 genotypes in both AUD (p = 0.015) and controls (p = 0.016). Only among controls, neuroticism personality scores mediated the relationship between genotype and sleep disturbance. Objective sleep measures (sleep efficiency, wake bouts and wake after sleep onset), differed significantly by CNR1 rs806368 genotype, both at baseline (p = 0.023, 0.029, 0.015 respectively) and at follow-up (p = 0.004, p = 0.006, p = 0.007 respectively), and by FAAH genotype for actigraphy recorded sleep duration at follow-up (p = 0.018). These relationships suggest a significant role of the ECS in alcohol-related sleep phenotypes.